2019
DOI: 10.1177/0194599819846073
|View full text |Cite
|
Sign up to set email alerts
|

Organ Function Preservation Failure after (Chemo)Radiotherapy in Head and Neck Cancer: A Retrospective Cohort Analysis

Abstract: Objective The aim of the current study was to determine the incidence of organ function preservation failure (OFPF) in patients with head and neck squamous cell carcinoma (HNSCC) treated by (chemo)radiotherapy and to identify its risk factors. Study Design Retrospective cohort analysis. Setting Tertiary cancer care center. Subjects and Methods A single-center retrospective cohort analysis was done (n = 703) in which OFPF after (chemo)radiotherapy was assessed. OFPF was defined as local failure or pure function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 28 publications
1
10
1
Order By: Relevance
“…[14][15][16] This is due to the limited response rates (RRs) with the current treatment options, which are often associated with serious side effects. [17][18][19] Therefore, it is becoming more important to further unravel the molecular carcinogenesis of HNSCC. This can elucidate the genetic and biological heterogeneity of the disease as well as the importance of interindividual variation in the human genome for therapy selection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] This is due to the limited response rates (RRs) with the current treatment options, which are often associated with serious side effects. [17][18][19] Therefore, it is becoming more important to further unravel the molecular carcinogenesis of HNSCC. This can elucidate the genetic and biological heterogeneity of the disease as well as the importance of interindividual variation in the human genome for therapy selection.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this increasing knowledge of the molecular characteristics of HNSCC, the 5‐year survival remains relatively low, especially in the HPV‐negative cohort (48% in HPV‐negative and 80% in HPV‐positive HNSCC) 14–16 . This is due to the limited response rates (RRs) with the current treatment options, which are often associated with serious side effects 17–19 . Therefore, it is becoming more important to further unravel the molecular carcinogenesis of HNSCC.…”
Section: Introductionmentioning
confidence: 99%
“…Of interest, almost all the patients wearing tracheostomy had T3/T4-stage lesions, reflecting the tracheostomy as a surrogate for locally advanced tumors with airway comprises. Later, in a single-institution study investigating the factor predicting organ preservation failure after CCRT, Heukelom et al 37 also identified T4 lesion and pretreatment tracheostomy as independent prognostic factors in laryngeal and hypopharyngeal cancers. Our results are consistent with these findings that the tracheostomy prior to, or during, the radiotherapy may be a surrogate for an advanced T stage.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, their results showed that patients who underwent pretreatment tracheotomy had a statistically significant decrease in both OS (HR 1.55, 95% CI=1.03−2.34, P =0.03) and DFS (HR 1.54, 95% CI = 2.07−2.22, P =0.02) ( 15 ). Some studies have also revealed that pretreatment tracheotomy was a strong predictor for long-term tracheostomy after organ-preservation strategy in laryngeal and hypopharyngeal cancers ( 16 , 17 ). In our study, which focused on HPSCC patients with pretreatment cord dysfunction, pretreatment tracheotomy was associated with OS only in the univariate analysis, but the difference was not statistically significant in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%